A Concept of Liability for the Government's Negligence in the Prevention of Wildfires in Indonesia - Mardhatillah, Siti Ruhama; ., Ridwan (KnE Social Sciences, 2023)
Wildfire is considered an annual problem in Indonesia. Based on the polluter-pays principle, the environmental damage that occurred from the fires must hence be borne by the injurers through the provided liability mechanisms. The Indonesian liability system, however, still focuses merely on how private entities as the bearers of the permits are being held liable, with no attempts to reach other potentially liable parties. The liability system has not considered the governments negligence in the issuance of the permit, fulfilling the statutory duties, or failures to supervise the permitted activities. This research attempts to investigate the concept of government liability for wildfires in Indonesia by analyzing some doctrines and legal principles as the bases for imposing liability in different jurisdictions (the liability trends in developing countries, the US, and the Netherlands). The results are: first, each country adopts its own doctrine and legal principle in imposing liability on their governments. However, in general, most countries acknowledge that they cannot impose liability to the government when they act in terms of discretions, policies, and choices in which they have multiple interests to consider. Second, government liability in Indonesia has been laid down under the Article 1365 of the Civil Code and the Law Number 30 of 2014 on Government Administration. As for the prevention of wildfires, the authors recommend applying the concept of a multi-task/single-task agent to consider to what extent the liability can be held against each government agency based on their statutory duties. Keywords: liability, government, negligence, wildfires